Land Characteristics Study as Halal Tourism Destination Supporting Factors at Benang Kelambu Waterfall in Central Lombok Regency of West Nusa Tenggara Province - Febriani, Trina; Dasrizal, Dasrizal; Sutrisna, Nana (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
Land is one of supporting factors of Halal Tourism Destination at Benang Kelambu Waterfall in Central Lombok Regency. This research was aimed to collect, process, analyse the data and discuss about land characteristics as supporting factors of Benang Kelambu Waterfall Halal. This study used a descriptive analysis method. This study was focus on 1) Describing the land characteristics in supporting the development of Benang Kelambu Waterfall tourism destination. 2) Describing the concept of land use related to supporting factors of Benang Kelambu Waterfall Halal Tourism Destination. The land characteristics include the topography, region, soil type and climate. In this research, factors in developing concept of tourism were tourism potential, tourist attraction, tourism land resources, accessibility, facility and infrastructure, and land use management. After processing and analyzing collected data, Benang Kelambu Waterfall was rated as 83-101 or classified as cultivation and forest area so that it could be managed and used for tourism area.